Schools and Skills in Developing Countries: Education Policies and Socioeconomic Outcomes - Glewwe, Paul (Journal of Economic Literature, 2002)
This paper reviews recent research on the determinants of educational outcomes, and the impact of those outcomes on other socioeconomic phenomena. It addresses three questions: 1) What school policies are most cost-effective in producing students with particular cognitive skills, such as literacy and numeracy? 2) What is the relationship between schooling, particularly cognitive skills acquired in school, and labor productivity? 3) What impact does schooling, especially cognitive skills, have on other socioeconomic outcomes? While recent research has made some progress, these are difficult questions and much more work is needed. The paper provides suggestions for future research on these questions.